Constructing Indicators For Islamic Financial Inclusion - Fauz Moh'd Khamis; Mohamad Yazid Bin Isa; Noraini Yusuff (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2021)
This study conceptualizes and proposes the measurement items and constructs for assessing the financial inclusion of Islamic finance. It proposes and validates the demand-side measurement tool for the financial inclusion of Islamic finance using four dimensions, i.e., quality, accessibility, usage, and satisfaction. The measurement instrument proposed in this study assesses the actual performance of Islamic finance towards total financial inclusion. The study was based on exploratory factor analysis of the questionnaire responses collected from 129 respondents. The questionnaires were distributed to the Zanzibar residents from February 2021 to March 2021. The questionnaires are adapted mainly from the Findex Survey (2017). The financial inclusion of Islamic finance can be determined using four dimensions (components); relevancy (quality) of Islamic financial services, accessibility of Islamic financial services, usage of Islamic financial services, and satisfaction with Islamic financial services. The study is limited to Principal Components Analysis as a factor analysis approach. Besides, the study has been conducted in Zanzibar, a semi-autonomous nation in East Africa. Therefore, more comprehensive studies are required in various areas for generalizing the results.